Perceptions of resilience, collective action and natural resources management in socio-ecological production landscapes in East Africa - Bedmar Villanueva, Ana; Morimoto, Y.; Maundu, P.; Jha, Y.; Otieno, G.; Nankya, R.; Ogwal, R.; Leles, B.; Halewood, Michael (United Nations University, 2018)
If properly managed, socio-ecological production landscapes and the ecosystem services they provide can contribute to the well-being of local communities, as well as to the achievement of the global conservation agenda and of other relevant development policies at the national level. However, many of these landscapes worldwide are often highly insecure due to unsupportive government policies, agencies, and lack of local collective action. By conducting a network analysis and participatory exercises with district officials and farmers in two communities from Rakai (Uganda) and Lushoto (Tanzania) districts, we studied local perceptions regarding (a) the contribution of natural resources to local farmers’ livelihoods, and how these farmers, in turn, contribute to the conservation and sustainable use of these natural resources, (b) landscape threats and resilience, and (c) major causes of the identified and possible local solutions for mitigating them. The study shows that in the four communities there was very little communication among farmers and that the cooperation between farmers and local and district stakeholders was rather limited. Farmers did not seek much information concerning conservation and use of natural resources and very few of them were aware of the existence of government programs regulating natural resources management. In addition, the study sites were found to be experiencing a progressive degradation of their natural resources. We, therefore, conclude that the creation of spaces for informed, public discussion aimed at making the institutional context more favourable for the creation and coordination of community groups and at enhancing their interaction, would contribute to a wider movement of knowledge and social exchange. This, in turn, could ultimately result in the creation of local initiatives aimed at the conservation of natural resources.